Ակն գավառակի հայ բնակչությունը 1830–1880-ական թվականներին - Բաբլումյան, Ա. (ՀՀ ԳԱԱ հրատ.)
Akn region is situated in the southwestern part of Western Armenia. This region was formerly part of Sebastia eyalet and later of Kharberd vilayet. In the territory of Akn region there were numerous settlements populated by Armenians forcibly Islamized in the 17th–18th centuries.Область Акн находится в юго-западной части Западной Армении. Данная область являлась частью эйалета Себастия, впоследствии вилайета Харберд.
Keywords: Հայագիտություն; Պատմություն